Implementation of Picture Strip Story Teach Reading Comprehension of SMP TQ Ibaadurrohman Way Jepara - Rangga Mega Putra; Ruri Supatmi (LPPM Universitas Pahlawan Tuanku Tambusai, Riau, Indonesia, 2022)
The method of this research was qualitative descriptive methodology. This research was conducted in the eighth grade students of SMP TQ Ibaadurrohman Way Jepara. The subjects of this research would be observed by research was teacher and students. The researcher observed eight class with one English teacher who teaching in the eighth grade. There were two classes namely VIII-A and VIII-B with consisted of 20, 20 students each class. The researcher took all students from each class as the subject of this research so that the total of all the students taken by the researcher was 40 students. In post-test of cycle 2, the results of the research from qualitative data. It showed the students get higher score of pronunciation test after using this technique. There are 35 students were categorized successful and passed. It means that the students’ reading comprehension was improved.